MITIGASI TSUNAMI DI KABUPATEN PURWOREJO, JAWA TENGAH BERBASIS KEANEKARAGAMAN VEGETASI - Slamet Mardiyanto Rahayu; Wiryanto Wiryanto; Sunarto Sunarto (Fish Scientiae, 2019)
Purworejo coastal area laid down in the critical area on nature disaster like tsunami. The aim of this research is determine of biodiversity vegetation as an efforts of tsunami mitigation in Purworejo coastal area, Central Java. This research conducted at August-September 2016 in beach and coastal area of Purworejo Regency, Central Java. It was three location including Gedangan Village, Jati kontal Village, and Ngentak Village.This research obtained that beach area of Purworejo Regency consist of 16 family and 18 plant species with the potencial species for tsunami mitigation are Casuarina equisetifolia, Terminalia catappa, and Hibiscus tiliaceus. The coastal area of Purworejo Regency are habitat of mangrove vegetation consist of 6 family and 8 plant species with the potencial species for tsunami mitigation are Rhizophora mucronata, R.stylosa, Sonneratia alba, S.caseolaris, and Nypa fruticans.